MORAL INSTINCT AND THE EVOLUTION OF ALTRUISM IN THE CONTEXT OF "NATUREMAN-SOCIETY" - Dilorom Yuldasheva (Western European Studies, 2024)
The current state of science requires deep philosophical understanding of life phenomena in the system "nature-man-society". This article explores the role of philosophy as a science of survival, focusing on the importance of bioethical trends and the integration of new views on life. We analyse the evolutionary change of the genome and the adaptation of living beings, emphasizing how instincts, including the moral instinct, shape human behaviour. Based on historical, philosophical and biological theories, the provisions on altruism as an evolutionarily sustainable strategy necessary for the survival of species are considered. We emphasize that altruism not only influences behaviour, but also forms the moral foundations of modern humanistic ideas, ensuring the creation of a social society of positive interactions and mutual assistance.
Keywords: philosophy; evolution; altruism; moral instinct